Profitability Analysis of Sharia Commercial Banks in Indonesia - Uswatun Khasanah; Indanazulfa Qurrota A’yun; Luk Luk Annisatul Mufida; Niken Riswamati (Universitas Darussalam Gontor, 2023)
Islamic banking needs to maintain its maximum performance. Banking performance as a whole can be seen through the value of profitability. It is important to know because the banking condition in the future can be seen and predicted through its financial performance. Therefore, this study aims to analyze the profitability of Islamic commercial banks in Indonesia. This study uses quantitative methods with panel data regression estimates during the 2015Q1-2020Q4 period at 5 Islamic Commercial Banks in Indonesia, namely BRI Syariah Bank, BNI Syariah Bank, BCA Syariah Bank, Mega Syariah Bank, and BTPN Syariah Bank at 5 Syariah Commercial Banks. in the period 2010-2019. The variables used are ROA, CAR, NPF, FDR and BOPO. Stages of panel data to select the best model required several tests, namely the Chow test, Housman test and LM test. Next, it is necessary to test the classical assumptions in the form of heteroscedasticity test, multicollinearity test and autocorrelation test. The results showed that simultaneously the independent variables CAR, NPF, FDR and BOPO had a significant effect on profitability (ROA). Partially, the CAR and NPF has insignificant effect on profitability (ROA). Then, the FDR variable partially has a positive and significant effect on profitability (ROA). The BOPO variable has a negative and significant effect on profitability (ROA).